The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s40090-019-00194-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical modeling of substrate and biomass effluents in up-flow anaerobic sludge blanket (UASB) biogas reactor

Abstract: Organic liquid waste from food production industry is inevitable. High chemical oxygen demand (COD) contents in organic liquid waste could disrupt the water ecosystem. On the other hand, COD contents can be reduced and utilized to produce biogas by UASB reactor. However, there is a problem in operating UASB reactor, namely the high biomass content in methanogenic granule form, which is washed out with the effluent. The influent flow rate affects biomass content and the suitable flow rate is important for the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This was because an increase in pH in the range of 6.3–7.8 increase methanogenesis [ 35 , 36 ]. The plot also showed that at pH 7, the % removal of COD was seen to be maximum at a temperature of 24.5 °C beyond this pH the % removal of COD was decreased this is because methanogenesis process is hindered [ 37 , 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This was because an increase in pH in the range of 6.3–7.8 increase methanogenesis [ 35 , 36 ]. The plot also showed that at pH 7, the % removal of COD was seen to be maximum at a temperature of 24.5 °C beyond this pH the % removal of COD was decreased this is because methanogenesis process is hindered [ 37 , 38 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%